2021
DOI: 10.3390/biomedicines9030297
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Ursolic Acid through Mediating the Inhibition of STAT3/PD-L1 Signaling in Non-Small Cell Lung Cancer Cells

Abstract: Targeted therapy based on natural compounds is one of the best approaches against non-small cell lung cancer. Ursolic acid (UA), a pentacyclic triterpenoid derived from medicinal herbs, has anticancer activity. Studies on the molecular mechanism underlying UAʹs anticancer activity are ongoing. Here, we demonstrated UAʹs anticancer activity and the underlying signaling mechanisms. We used Western blotting and real-time quantitative polymerase chain reaction for molecular signaling analysis. We also used in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 56 publications
(31 reference statements)
1
32
0
Order By: Relevance
“…The anti-tumor activity of ursolic acid can be partly attributed to its binding to EGFR and subsequent down-regulation of phospho-EGFR and inhibition of the JAK2/STAT3 signaling pathway. In addition, ursolic acid reduces VEGF, MMP, and PD-L1 expression, as well as STAT3/MMP2 and STAT3/PD-L1 complex formation, observations reported in non-small cell lung cancer cells [105]. Conway et al noted that ursolic acid inhibited collective cell migration while promoting lysosome-associated cell death, outcomes that were JNK-dependent in glioblastoma multiforme cells [106].…”
Section: Ursolic Acidmentioning
confidence: 84%
See 1 more Smart Citation
“…The anti-tumor activity of ursolic acid can be partly attributed to its binding to EGFR and subsequent down-regulation of phospho-EGFR and inhibition of the JAK2/STAT3 signaling pathway. In addition, ursolic acid reduces VEGF, MMP, and PD-L1 expression, as well as STAT3/MMP2 and STAT3/PD-L1 complex formation, observations reported in non-small cell lung cancer cells [105]. Conway et al noted that ursolic acid inhibited collective cell migration while promoting lysosome-associated cell death, outcomes that were JNK-dependent in glioblastoma multiforme cells [106].…”
Section: Ursolic Acidmentioning
confidence: 84%
“…Ursolic acid Apple peels ↑ sFRP4, sp1, Caveolin-1, Bax, p21, p53, Cyclin B1, Caspase-3, Caspase-8, Caspase-9, fibronectin-1, E-Cad, and LC3-II Gliolastoma [104], breast [100,101], intestinal [102], lung [103], colorectal [105], esophageal [106], and pancreatic [107] [111], breast [112,113], prostate [115], ovarian [114], colorectal [116,117], lung [118], gastric [56], and endometrial [119] cancer ↓ MMP-2, FAK, CDK1, PSA, TMPRSS2, TMEPA1, PI3K, Akt, Bcl-2, TS, RhoA, Rac1, JAK/STAT3, MAPK, and NFκB Quercetin Apple, chili pepper, blueberry, cherry, cranberry, black tea, and red wine ↑ p53 Liver [120,121], prostate [122,123], colon [123], leukemia [123], lymphoma [123], breast [123,124], pancreatic [125], lung [126],…”
mentioning
confidence: 99%
“…In addition, a high level of PD-L1 has been confirmed to appear on the surface of different cancer cells, including NSCLC, justifying that its expression facilitates cancer cells to escape immune response [ 18 ]. PI3K/AKT and JAK/STAT pathways play a vital role in the expression of PD-L1 in tumor cells which takes part in different cancer hallmarks [ 19 , 20 ]. The PD-1/PD-L1 inhibitory checkpoint suppresses antitumor immune responses [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a secretion from the animal toad -Bufalin. Accumulating evidences have shown that natural compounds play an important role in the treatment of cancer, including inhibiting cancer cell proliferation and inducing apoptosis, as well as inhibiting cancer cell metastasis and angiogenesis (Liu et al, 2019a;Sun et al, 2019;Liu et al, 2020;Kang et al, 2021). More interestingly, in the treatment of tumors, multiple natural compounds are reported to exert therapeutic effect by targeting autophagy (Towers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%